1984
DOI: 10.1056/nejm198412203112504
|View full text |Cite
|
Sign up to set email alerts
|

Bone-Marrow Transplantation in the Maroteaux–Lamy Syndrome (Mucopolysaccharidosis Type VI)

Abstract: A 13-year-old girl with the severe form of the Maroteaux-Lamy syndrome (mucopolysaccharidosis Type VI, arylsulfatase B deficiency) has had successful reconstitution with bone marrow from her HLA-MLC-matched sister who had normal arylsulfatase B activity. Full engraftment has been present for 24 months. The following biochemical and clinical changes have occurred: arylsulfatase B activity in peripheral lymphocytes and granulocytes increased to normal levels, and the activity in serial liver-biopsy specimens inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
0
4

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(88 citation statements)
references
References 20 publications
3
81
0
4
Order By: Relevance
“…[13][14][15][16][17] Animal studies suggest that BMT has a place in the treatment of MPS VII. Birkenmier et al 9 reported that in adult MPS VII mice, BMT resulted in a significantly increased life span which was similar to that observed for normal mice given the same therapy.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17] Animal studies suggest that BMT has a place in the treatment of MPS VII. Birkenmier et al 9 reported that in adult MPS VII mice, BMT resulted in a significantly increased life span which was similar to that observed for normal mice given the same therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In the past 25 years, nearly a thousand patients with metabolic storage disorders have received allogeneic hematopoietic stem cell transplantation for curative purposes using bone marrow from HLA-matched or mismatched related donors. This results in clinical benefit by replacing the missing enzyme produced by the donor cells circulating in the blood [39][40][41][42][43].…”
Section: Non-oncologymentioning
confidence: 99%
“…The early onset and rapid progression of cardiovascular disease require management of symptoms (6)(7)(8)(9)(10). Therapeutic interventions for children and adults with LSD and later-onset heart problems include bone marrow (BM) transplantation postmyeloablation (11)(12)(13) and surgical replacement of damaged arteries and valves (14)(15)(16), although this treatment is rarely used (17). Both create attendant risks to the patient and neither are currently feasible treatments for infants, many of whom succumb to heart and respiratory problems within the first year of life.…”
mentioning
confidence: 99%